Welcome to Scribd. Sign in or start your free trial to enjoy unlimited e-books, audiobooks & documents.Find out more
Download
Standard view
Full view
of .
Look up keyword
Like this
1Activity
0 of .
Results for:
No results containing your search query
P. 1
Chapter 7 - Different at Ion

Chapter 7 - Different at Ion

Ratings: (0)|Views: 1|Likes:

More info:

Published by: Wan Muhammad Abdul Hakim on Feb 20, 2012
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as PDF, TXT or read online from Scribd
See more
See less

09/22/2014

pdf

text

original

 
 
QQM1023 Managerial MathematicsChapter 7: Differentiation 170
 7.1 THE CONCEPT OF DIFFERENTIATION
If
 f 
defined as the function of
 x
and can be written as
( )
 x f 
.Then the derivative of
( )
 x f 
denoted as
( )
 x f 
or 
dxdy
is read as‘derivative value of function
 f 
at
 x
’. The
( )
 x f 
known as the FIRSTDIFFERENTIATION/ FIRST DERIVATIVE of
 f 
 
at
 x
.
7.2
 
DIFFERENTIATION USING FIRST PRINCIPLE(The concept of limit)
Consider a function of
 f 
and assume that 2 points were at the curveof a function
 f 
, i.e
( )( )
 x f  x A
,
=
and
( )( )
h x f h x B
++=
,
 
)(/
 x f  y
 
 x
 
h x
+
 
 x
 
Chord ( 
 AB)
 
 P Q
 f(x) f(x+h)(x , f(x)) =
 
A
 
((x+h), f(x+h)) =
 
 B
 
Tangent ( 
 PQ)
 
0
 x ydxdy
δ  δ  
,
 
 
 
QQM1023 Managerial MathematicsChapter 7: Differentiation 171
( )( ) ( )
h x f h x f   x f dxdy
h
+==
0
lim
 
From the diagram above,
 
The straight line
 PQ
is called a tangent to function
 f 
at thepoint
 x
.
 
The slope / gradient of tangent
 PQ
is an approximation ofchord
 AB
at that curve, i.e:Slope / Gradient of
( ) ( )( )
1
+=
h x f h x f   AB
 When
0
h
, equation
( )
1
can be written as
( ) ( )( )
2lim
0
+
h x f h x f 
h
 
 
Since the gradient of function
 f 
at
 x
equals to the gradient ofa tangent
 PQ
(equation
( )
2
), then equation
( )
2
named as thefirst principle differentiation or derivative :If
( )
26
+=
 x x f 
, find
( )
 x f 
by using the first principledifferentiation method.Solution:By using:
( )( ) ( )( )
ah x f h x f   x f 
h
+=
0
lim
 
Example 1:
 
 
QQM1023 Managerial MathematicsChapter 7: Differentiation 172
 Given
( )
26
+=
 x x f 
, then
( ) ( )
26
++=+
h xh x f 
 Substitute
( ) ( )
26
++=+
h xh x f 
in
( )
a
 
( )( ) ( )
h x f h x  x f 
h
++=
26lim
0
 
( )( )
[ ]
h xh x x f 
h
2626 lim
0
+++ =
 
( )
h xh x x f 
h
26266 lim
0
++ =
 
( )
6lim6lim
00
==
hh
hh x f 
 Using the concept of limits,
66
0
=
h
had 
, therefore ;
( )
6
=
 x f 
 Find the first derivative (
( )
dxdyor  x f 
) of the following functions byusing the first principle method:a)
( )
13
=
 x x f 
 b)
1
2
=
 x y
 
 
Step 1:Step 2:
Exercise:

You're Reading a Free Preview

Download
scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->